2018
DOI: 10.1007/s00264-018-4041-5
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre comparative study of Z-shape elevating–pulling reduction and skull traction reduction for treatment of lower cervical locked facets

Abstract: Halo vest-assisted Z-shape elevating-pulling reduction appears to be a simple, safe, and effective technique for pre-operative reduction of lower cervical locked facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Children with congenital dysplasia benefit from early diagnosis and reasonable treatment to achieve a favorable prognosis [ 17 , 18 ], but there are still some cases with delayed diagnosis or poor conservative treatment efficacy that require surgical treatment. Surgical treatment is mainly to restore the concentric relationship between the femoral head and the acetabulum, whilst avoiding femoral head necrosis and reoperation [ 19 , 20 ]. Traction + reposition + hip spica cast is a common clinical treatment for DDH.…”
Section: Discussionmentioning
confidence: 99%
“…Children with congenital dysplasia benefit from early diagnosis and reasonable treatment to achieve a favorable prognosis [ 17 , 18 ], but there are still some cases with delayed diagnosis or poor conservative treatment efficacy that require surgical treatment. Surgical treatment is mainly to restore the concentric relationship between the femoral head and the acetabulum, whilst avoiding femoral head necrosis and reoperation [ 19 , 20 ]. Traction + reposition + hip spica cast is a common clinical treatment for DDH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reduction is easy. 10 A review reported a combined success rate of 80% for MUA, manual, and traction reductions. 23 Our study's success rate for manual reduction was 93%.…”
Section: Reduction Methods and Reduction Success Ratementioning
confidence: 99%
“…Various factors affect the success rate of reduction, such as time from injury to reduction, type of dislocation, and presence of fracture of articular processes. 10 For cases in which the injury is long-standing and the rate of healing is poor, neurological complications will occur. 5 In this study, all cases of failed manual reduction were C6/7 dislocations in group L. The low success rate of manual reduction for C6/7 dislocations can be attributed to the difficulty in observing the dislocation site on fluoroscopy; additionally, the dislocation site is far from the head, making applying force difficult.…”
Section: Failure Factors Of Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors have then performed a multicenter study in 63 patients with locked facets. 47 Z-shape elevating-pulling reduction (n = 20) or traditional skull traction reduction (n = 43). The success rates were significantly better in the Z-shape elevating group (87.5%) than in the skull traction group (35.3%) for unilateral locked facet reduction.…”
Section: (3) Publications Defending Closed Reductionmentioning
confidence: 99%